2015
DOI: 10.1097/bsd.0b013e31827a32ee
|View full text |Cite
|
Sign up to set email alerts
|

3D-FSE Isotropic MRI of the Lumbar Spine

Abstract: This systematic evaluation showed that there is a very high degree of agreement between diagnostic findings assessed on 3D-TSE and conventional 2D-FSE sequences. Overall, intermethod agreement was statistically noninferior to the intraobserver agreement between repeated 2D-FSE evaluations. Overall, this study shows that 3D-TSE performs equivalently, if not superiorly to 2D-FSE sequences. Reviewers found particular utility for the ability to manipulate image planes with the 3D-TSE if there was greater pathology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 14 publications
0
14
1
Order By: Relevance
“…In spine imaging, most of the studies using 3D isotropic sequences were feasibility studies reporting less artifacts and better delineation of small structures, or studies evaluating inter-method and inter-observer agreement (91011121314). Recently, Lee et al (15) compared 3D T2-weighted turbo spin-echo (TSE) and 2D T2-weighted TSE sequences of the lumbar spine, with surgical findings and symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…In spine imaging, most of the studies using 3D isotropic sequences were feasibility studies reporting less artifacts and better delineation of small structures, or studies evaluating inter-method and inter-observer agreement (91011121314). Recently, Lee et al (15) compared 3D T2-weighted turbo spin-echo (TSE) and 2D T2-weighted TSE sequences of the lumbar spine, with surgical findings and symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…The short T 2 relaxation constants of musculoskeletal tissue made the use of high turbo‐spin echo factors problematic due to the fast signal decay . More recently available improvements enabled the use of long echo trains for T 2 spin echo sequences and their clinical application with true T 2 contrast, improving diagnostic performance for the spine …”
mentioning
confidence: 99%
“…8 More recently available improvements enabled the use of long echo trains for T 2 spin echo sequences and their clinical application with true T 2 contrast, improving diagnostic performance for the spine. 9,10 Despite these recent technical improvements, 2D sequences have widely remained the standard in clinical routine, mostly due to shorter scan times. Despite the use of parallel imaging, the accelerated 3D sequences still require 6 to 7 minutes of scan time.…”
mentioning
confidence: 99%
“…1 Studies have evaluated the advantages of 3D T2WI sequences in brain 2 and head and neck imaging 3,4 ; however, there have only been a small number of studies investigating their value in spine MR imaging. [5][6][7] Most of these studies have compared the visualization of degenerative disease of the lumbar spine on conventional T2-FSE sequences versus 3D T2WI sequences. Lee et al 7 reported no statistically significant difference between the sensitivities of T2-FSE and 3D T2-SPACE for the detection of neural foraminal stenosis, spinal canal stenosis, and nerve compression at 3T.…”
mentioning
confidence: 99%
“…Lee et al 7 reported no statistically significant difference between the sensitivities of T2-FSE and 3D T2-SPACE for the detection of neural foraminal stenosis, spinal canal stenosis, and nerve compression at 3T. Furthermore, Blizzard et al 5 found a high degree of interobserver agreement between T2-FSE and T2-SPACE images for the evaluation of spinal canal stenosis, disc herniation, and degenerative changes. A similar study comparing T2-FSE and T2-SPACE also found high interobserver agreement for the visualization of C-spine degenerative disease.…”
mentioning
confidence: 99%